2012
DOI: 10.1007/s11748-012-0180-6
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment for primary lung cancer combined with idiopathic pulmonary fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is defined as a specific form of chronic, progressive fibrosing interstitial pneumonia of unknown cause. IPF is associated with an increased risk of lung cancer, and lung cancer patients with IPF undergoing pulmonary resection for non-small cell lung cancer have increased postoperative morbidity and mortality. Especially, postoperative acute exacerbation of IPF (AEIPF) causes fatal status and long-term outcomes are worse than for patients without IPF, although certain subgro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 57 publications
1
28
0
Order By: Relevance
“…IPF is associated with an increased risk of lung cancer, with a relative risk of 7.0-14.0 (compared with the general population) (7). Approximately 2% to 4% of lung cancer patients have IPF (2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IPF is associated with an increased risk of lung cancer, with a relative risk of 7.0-14.0 (compared with the general population) (7). Approximately 2% to 4% of lung cancer patients have IPF (2).…”
Section: Discussionmentioning
confidence: 99%
“…IPF is associated with an increased risk of lung cancer. The prevalence of lung cancer in patients with IPF is high, ranging from 4.8% to 48% (3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with IPF have shown markedly higher rates of postoperative pulmonary morbidity (26%) and mortality (8%) after surgical resection for lung cancer as compared to those without IPF [8,9]. Several studies have shown that other types of ILD also influence PPCs and mortality after lung surgery [10], and the patients with ILD had a higher incidence of these complications compared to those without ILD after lung resection.…”
Section: Introductionmentioning
confidence: 99%
“…Interstitial pneumonia and emphysema provoke more risks for postoperative complications and mortality. [10,1822] Here, we identified a predictive factor for postoperative mortality in patients with NSCLC and CPFE in a multiinstitutional setting.…”
Section: Discussionmentioning
confidence: 99%
“…These rates were also higher than previous postoperative 30-day mortality and complication rates for NSCLC in Japan (0%–0.9% and about 20%, respectively). [18,20,2225] . Hence, modalities for treating NSCLC in patients with CPFE should be carefully determined.…”
Section: Discussionmentioning
confidence: 99%